Financial Transparency at Stake: Unraveling the Determinants of Audit Delay - Sorongan, Fangky Antoneus; Pardede, Tiolina Evi; Silitonga, Niko (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The timely dissemination of financial information stands as a cornerstone of transparency and efficiency in modern capital markets. Audit delay, broadly defined as the interval between the financial year-end and the date of issuance of the auditor's report, represents a critical metric of reporting timeliness. The duration of this delay is directly correlated with the time auditors spend on fieldwork, implying that lengthier audit engagements result in extended reporting lags. Consequently, undue delays can significantly diminish the utility of such information for decision-making purposes. This research aims to meticulously re-examine the influence of company size, profitability, solvency, and audit opinion on audit delay within the Indonesian manufacturing sector for the period spanning 2020 to 2024. Using a quantitative method with a secondary approach, the sample was selected using a purposive sampling method, and the data was processed using Eviews and SPSS for multiple linear regression analysis. The results indicate that company size, profitability (ROA), and solvency (DER) have a significant partial effect on audit delay, while audit opinion has no significant partial effect on audit delay. The research model passed the classical assumption test, meeting the assumption of normality and showing no signs of heteroscedasticity, multicollinearity, or autocorrelation. The adjusted R-squared value is 0.237, or 23.7%, indicating that 23.7% of the effect of audit delay can be explained by the variables of company size, solvency, profitability, and auditor opinion, while 76.3% can be explained by other causal factors not included in this study.